1) 2 (11х - 5) - 17х = 55;2 * 11x + 2 * (- 5) - 17x = 55;22x - 10 - 17x = 55;5x - 10 = 55;5x = 55 + 10;5x = 65;x = 65 : 5;x = 13.Ответ. 13.2) 5 (8х + 3) - 12 = 83;5 * 8x + 5 * 3 - 12 = 83;40x + 15 - 12 = 83;40x + 3 = 83;40x = 83 - 3;40x = 80;x = 80 : 40;x = 2.Ответ. 2.3) 7 (2х + 9) + 3х = 114;7 * 2x + 7 * 9 + 3x = 114;14x + 63 + 3x = 114;17x + 63 = 114;17x = 114 - 63;17x = 51;x = 51 : 17;x = 3.Ответ. 3.4) 3 (4х + 13) - 25 = 74;3 * 4x + 3 * 13 - 25 = 74;12x + 39 - 25 = 74;12x + 14 = 74;12x = 74 - 14;12x = 60;x = 60 : 12;x = 5.Ответ. 5.